KONTRIBUSI KEBUGARAN JASMANI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS KHUSUS OLAHRAGA SEKOLAH MENENGAH PERTAMA NEGERI 1 KOTA BUKITTINGGI - Emil Mon (Jurnal MensSana, 2017)
Based on obsevation at the Student of sport in SMP N 1 Bukittinggi City showed the learning outcomes is still low. This is estimated influence by pphysical fitness and learning motivatio. This study aims to know the contribution of physical fitness and learning motivation to learning outcames of student’s Sport in SMP N 1 Bukittinggi City. This reasearch medthod is correlation, to know how big the contribution one variable each other. The population are student of Sport in SMP N 1 BukittinggiCity in the academic year 2014/ 205 with amount 30 student. The sampling technique is total sampling, so the samples are 30 student. Data was collected by physical fitness test instrument Indonesia aged 13 to 15 year and completed questionnaires to measure physical fitnessand learning motivation, and learning outcomes used 2nd data of student’s report in 2015/2016 acamic year. The results showed that: (1) physical fitness had a significant contribution with tcount (3,71) >ttable(1,70) and give contribution for 32,95% to learning outcomes. (2) Learning motivation had a significant contribution with tcount (5,60) > ttable(1,70) and give contribution for 52,85% to the learning outcomes. (3) physical fitness and leaning motivation have significant contribution with F count (42,948) > Ftable (3,35) And countributed together by 76.04% to learning outcomes.